Adult attachment in clinical social work practice, research, and policy - Bennett, Susanne; Nelson, Judith Kay 1941- (Essential Clinical Social Work Series, 2010)
As John Bowlby's studies of human attachment revolutionized developmental psychology in the 1960s, adult attachment concepts have similarly transformed social work in recent years, leading to a generation of innovative attachment-based clinical practice. Adult Attachment in Clinical Social Work highlights social works contributions to attachment theory and research and the potential of these contributions to enhance clinical practice, inform social policy, and further empirical investigations. Designed for readers new to adult attachment, as well as those familiar with it, this book examines the current state of the field, reviewing assessment measures and research methods, summarizing new findings and ongoing controversies, and clarifying terms toward a common language. Clinical applications in individual, family, and group contexts are featured, with case examples from various populations and settings demonstrating the practical utility of the theory and its application to cross-cultural treatment. Later chapters move beyond discrete cases to attachment issues that impact society as a whole (e.g., adoption, elder care) and training issues that affect future generations of clinicians. Among the topics covered: Separation, loss, and grief in adults. The impact of neurobiology on affect regulation,  Applications of attachment concepts to interventions with at-risk families of young children, adolescents, and elder adults Clinical approaches for hard-to-reach individual clients and adults in group settings. The function of attachment in both familial and professional caregiving ?Policy implications of adult attachment relevant to family preservation Adult Attachment in Clinical Social Work is an essential text, breaking new ground in the attachment literature with immediate relevance for professionals and scholars in clinical social work and related mental health professions.